Effects of Supplementation with Corn or Dried Distillers Grains on Gains of Heifer Calves Grazing Smooth Bromegrass Pastures - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 60 heifer calves grazing smooth bromegrass pastures were used to compare supplementation of 0.5% of body weight per head daily of corn or dried distillers grains (DDG) in 2014 and 2015. Daily gains of heifers supplemented with corn or DDG were similar (P>0.05).
Keywords: Beef cattle